Notes on the systematic placement of Sciacharis (Anthicimimus) (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2015)
The entangled history of Sciacharis Broun, 1983, a genus in which nearly 240 species were placed by Herbert Franz who has apparently never studied its type species, was recently summarized by Jałoszyński (2014a, b). A synonymy of Chatchamaenus Franz with Sciacharis s. str. was demonstrated, and Maorinus Franz, 1980 was placed as a subgenus of Sciacharis (Jałoszyński 2014a). Still, the systematics of Sciacharis, a genus currently comprising nearly 300 species and distributed in the Southern Hemisphere, is far from clarity.